2021
DOI: 10.3390/diagnostics11071263
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Radiomics MRI Model for Survival Prediction of Recurrent Glioblastomas Treated with Bevacizumab

Abstract: Anti-angiogenic therapy with bevacizumab is a widely used therapeutic option for recurrent glioblastoma (GBM). Nevertheless, the therapeutic response remains highly heterogeneous among GBM patients with discordant outcomes. Recent data have shown that radiomics, an advanced recent imaging analysis method, can help to predict both prognosis and therapy in a multitude of solid tumours. The objective of this study was to identify novel biomarkers, extracted from MRI and clinical data, which could predict overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Strength and sphericity were also important parameters in our model. These features were among those selected for the successful prediction of outcomes in GBM patients treated with bevacizumab in a previous publication [32]. Adding age as a clinical variable, which also appeared in several reported survival models, appeared to be highly relevant in both our cohorts.…”
Section: Discussionmentioning
confidence: 85%
“…Strength and sphericity were also important parameters in our model. These features were among those selected for the successful prediction of outcomes in GBM patients treated with bevacizumab in a previous publication [32]. Adding age as a clinical variable, which also appeared in several reported survival models, appeared to be highly relevant in both our cohorts.…”
Section: Discussionmentioning
confidence: 85%
“…In a study by Bae et al [23], the authors found that adding radiomic features to patients' genetic and clinical profiles can improve survival prediction. Other studies reached a similar conclusion as MRI-based radiomics and machine learning (ML) algorithms could predict the OS of patients with decent statistics [24][25][26][27]. While several studies reported on the use of radiomics in neurodegenerative disorders or GBM, most have utilized ML to binary (high vs. low risk or short vs. long survival time) or multiple (high, intermediate, and low risk or short, intermediate, and long survival time) classification of OS in GBM patients.…”
Section: Introductionmentioning
confidence: 63%
“…They computed C-index using eight traditional and three As mentioned earlier, we used only radiomic features and clinical variables for OS prediction. Similar to our approach, Ammari et al [24] utilized radiomics and clinical data to stratify patients based on their survival. Using ML regression algorithms, they achieved a C-index of 0.64 for the prediction of OS.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of radiomics presented a novel non-invasive strategy to build survival risk models as well as to monitor response to various treatments, including ICIs [13,14,37,38]. Despite the growing field of biomarker research in immuno-oncology, none of these prognostic and predictive biomarkers have been translated to routine clinical use in the context of predicting patient outcomes to ICIs in a metastatic setting or to survival.…”
Section: Discussionmentioning
confidence: 99%